2017
DOI: 10.1371/journal.pone.0183773
|View full text |Cite
|
Sign up to set email alerts
|

Prickle1 regulates neurite outgrowth of apical spiral ganglion neurons but not hair cell polarity in the murine cochlea

Abstract: In the mammalian organ of Corti (OC), the stereocilia on the apical surface of hair cells (HCs) are uniformly organized in a neural to abneural axis (or medial-laterally). This organization is regulated by planar cell polarity (PCP) signaling. Mutations of PCP genes, such as Vangl2, Dvl1/2, Celsr1, and Fzd3/6, affect the formation of HC orientation to varying degrees. Prickle1 is a PCP signaling gene that belongs to the prickle / espinas / testin family. Prickle1 protein is shown to be asymmetrically localized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 70 publications
4
26
0
Order By: Relevance
“…In conclusion, the data presented here demonstrate that inner ear afferents are targeted to their specific nuclei within the hindbrain likely by yet unidentified molecule(s) and that these molecules are present for some period of time, conserved across amniote species, and conserved between the hindbrain and spinal cord. Evidence presented here and in recent papers on other tetrapods 16 , 17 , 42 , 50 implicate that the molecular gradients associated with dorsoventral patterning of the hindbrain and spinal cord, such as Wnt signaling 22 , may be involved in inner ear afferent central pathfinding. Future directions are to identify these molecules and investigate their role in guiding inner ear afferent central projections through a combination of molecular manipulations and transplantations.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…In conclusion, the data presented here demonstrate that inner ear afferents are targeted to their specific nuclei within the hindbrain likely by yet unidentified molecule(s) and that these molecules are present for some period of time, conserved across amniote species, and conserved between the hindbrain and spinal cord. Evidence presented here and in recent papers on other tetrapods 16 , 17 , 42 , 50 implicate that the molecular gradients associated with dorsoventral patterning of the hindbrain and spinal cord, such as Wnt signaling 22 , may be involved in inner ear afferent central pathfinding. Future directions are to identify these molecules and investigate their role in guiding inner ear afferent central projections through a combination of molecular manipulations and transplantations.…”
Section: Discussionsupporting
confidence: 64%
“…These conserved expression profiles are thus likely candidates for molecular guidance that provide a stereotyped pattern of innervation 10 , 11 . Consistent with the hypothesis that inner ear afferents might use diffusible molecules for central pathfinding, is that mutations in the Wnt-planar cell polarity pathway component, Prickle1, show aberrant central projections of inner ear afferents 22 . Furthermore, the dorsal Wnt gradients that are conserved between the hindbrain and spinal cord are not conserved with the midbrain due to absence of Lmx1b expression in that brain region that guides Wnt expression 25 .…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Expression of GATA3 and Prox1 ( Duncan and Fritzsch, 2013 ; Nishimura et al, 2017 ) showed an increased expression from day 5, which was then maintained until the last time point assessed (day 15). Additional SG markers, such as Islet1 ( Radde-Gallwitz et al, 2004 ), the NT receptor p75/NGFR ( von Bartheld et al, 1991 ; Sato et al, 2006 ), Prikle1 ( Yang et al, 2017 ), and Mafb ( Lu et al, 2011 ) were also up-regulated in a time-dependent manner. The intracellular filament peripherin was one of the latest markers starting to appear at day 12–15 of differentiation, which was concomitant with the morphological appearance of differentiated neuronal cells.…”
Section: Resultsmentioning
confidence: 99%
“…The central navigational properties of developing inner ear afferents is incompletely understood (Maklad and Fritzsch, ), but can be partially derailed in mutants of certain transcription factors such as Neurod1 (Jahan et al, ) and several others (Goodrich, ). In addition, afferent projections are established in a spatiotemporal progressing manner (Fritzsch et al, ; Zecca et al, ) likely using Wnt gradients to navigate (Fritzsch and Elliott, ; Yang et al, ) and can do so even if target nuclei are molecularly ablated (Elliott et al, ).…”
Section: Introductionmentioning
confidence: 99%